Pengaruh Konsentrasi Kolkisin Terhadap Keragaan Fenotipe Cabai Rawit Lokal (Capsicum frutescens l.) Asal Pulau Timor - Maria Afnita Lelang; Maria Krisanti Seran (Savana Cendana, 2020)
In Indonesia, Capsicum frutescens L. is an important horticultural commodity, seen from the area of production and its value as well as its large enough role to meet domestic needs as an export commodity and the food industry. However, chili production in Indonesia is still very low. One of the efforts that can be done is to carry out plant breeding using colchicine. Colchicine is one of the reagents for mutations that cause polyploidy, ie organisms have three or more sets of polyploid chromosomes in their cells. The purpose of this study was to determine the effect of colchicine concentration on the phenotype performance of local Capsicum frutescens L. from the island of Timor and to get the concentration that gave the best results on the phenotype performance of local Capsicum frutescens L. from the island of Timor. The research design used was a completely randomized design, with 3 treatments and 6 replications. The treatments consisted of control: plants without colchicine, colchicine concentration of 5 ppm, and colchicine concentration of 10 ppm. The results showed that colchicine treatment showed a significant effect on the observed parameters of the stem diameter of 14 DAS and 28 DAS, and canopy area 14 DAS. Treatment 5 ppm colchicine concentration resulted in optimum growth and yield.